Design and characteristics assessment of wireless vibration sensor for buildings and houses - Suherman Suherman; Fahmi Fahmi; Ulfa Hasnita; Zul Herri (Institute of Advanced Engineering and Science, 2021)
This paper reports the wireless vibration detector design and characterization for practical applications. System is built by using the ATmega microcontrollers, working on a free license 433 MHz frequency. Hardware characteristics are defined through experimental assessments. Assessment mainly on sensor output and sensor installation characteristics. As results, hardware is working as expected, where vibration level achieves at most 13% detection for 12 g vibration source. The vertical axis of the MPU6050 vibration detector results 87.5 times higher detection than in horizontal axis. Detected vibration increases from 1.03 g to 2.61 g when source-sensor distance is shortened from 10 cm to 2 cm. The aluminium sheet as sensor pad causes detection of 8.69 times higher than on ceramic pad. The lower the detection period the better the detection amplitude. However, the lower the period, the higher the consumed power. Microcontroller sleep mode is not suitable for short period detection. The node-based data validation to avoid transmitting false detection is not influencial for short period detection.